On the intriguing subject of the low amplitudes of magnetic anomalies at the Powell Basin - Catalán, M.; Negrete-Aranda, R.; Martos, Y. M.; Neumann, F.; Santamaría, A.; Fuentes, K. (Frontiers in Earth Science, 2023)
The Powell Basin is a small oceanic basin bounded by continental blocks that fragmented during break up of Antarctica from South America. This basin bounds the South Orkney Microcontinent to the east, the South Scotia Ridge to the north, and the Antarctic Peninsula to the west. The timing of its opening is poorly constrained due to the low amplitude of the oceanic spreading magnetic anomalies which hampers their identification and interpretation causing large uncertainties in proposed ages that range from the Late Eocene to Early Miocene. This basin has been extensively studied using a variety of geophysical methods including seismic, gravity and magnetics surveys intended to unveil the tectonic domains, the particularities of its magnetic anomalies and the understanding of the thermal regime in this area. Here, we show new magnetic and heat flow data integrated with other geophysical data from international databases (multichannel seismic data, bathymetry and free-air gravity), to analyze the thermal structure of the lithosphere of Powell Basin and the upper mantle dynamics as well as to discuss the probable causes of the abnormally small amplitudes of its magnetic anomalies. Our results show that the low magnetic anomaly amplitudes are not widespread but concentrate in the eastern and southwestern parts of the basin. We propose that these small amplitudes result from the thermal dependency of magnetic rocks caused by an asthenospheric branch flow that penetrates the Powell Basin through the northern area.